An Investigation into Primary School Teachers’ Perceptions of Grade Repetition as a Corrective Strategy for Low Academic Achievement - Rajkumar, Victoria Avian (My University, 2014)
This qualitative case study investigated teachers’ perceptions of the use of grade repetition as a corrective strategy for low academic achievement. Data were collected through interviews with three teachers at a denominational primary school in Trinidad and Tobago. The findings revealed that the teachers had concerns about this strategy, including the fact that repeaters were selected based on their readiness for the next level. Further, the participants indicated that grade repetition affected individual learners in different ways.
Keywords: Teacher attitudes; Primary school teachers; Educational strategies; Grade repetition; Academic achievement; Low achievers; Denominational schools; Trinidad and Tobago